Pengaruh Konseling Psikoanalisis Klasik Terhadap Perilaku Rasionalisasi Konseli - Irma Julita; Netrawati Netrawati; Yeni Karneli (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This research is motivated by the existence of inappropriate behavior in a student who often justifies his behavior even though the behavior he shows is wrong. The objective to be achieved in this study is to determine whether there is a significant difference before and after classical psychoanalytic counseling is carried out on rationalization behavior towards the client. This research method uses a pre-experimental one group, pre-test-post test approach. The population is one of the students of the State Islamic University of Bukittinggi. The data is processed using the Statistical Product and Service Solution (SPSS) version 26 program using the Wilcoxon test. The results obtained in this study were changes in values ​​between before and after counseling. Which means that there is a change in rationalization behavior before and after treatment is given. So it can be concluded that classical psychoanalytic counseling can be carried out in handling rationalization behavior towards the client. So, it is recommended that counselors when conducting counseling can use the classical psychoanalytic counseling model in dealing with one of the client's inappropriate behaviors, especially rationalization behavior.